ASSISTING GAME BASED LEARNING TO ENHANCE STUDENTS MOTIVATION AND PHYSICAL ACTIVITY IN PHYSICAL EDUCATION - Mirza; Agung Cahyadi; Imran Fadhil; Alyadi (Jurnal Pengabdian Bangsa, 2026)
This community service activity aimed to enhance students’ learning motivation and physical activity through learning assistance based on Game-Based Learning in Physical Education, Sports, and Health classes. The activity was conducted at SMP Negeri 2 Bireuen and involved students and physical education teachers as community service partners. The implementation method consisted of three stages: preparation, implementation, and evaluation, which included designing game-based activities, assisting the learning process, and conducting reflective discussions with teachers. The results of the activity indicated that the application of Game-Based Learning was able to create a more active and enjoyable learning atmosphere, thereby increasing students’ enthusiasm, participation, and engagement in physical activities during the learning process. In addition, this mentoring activity provided teachers with new experiences and insights in implementing innovative, student-centered learning models. Therefore, game-based learning is recommended as an alternative approach in physical education that can be sustainably applied to improve the quality of learning in schools.